β-thalassemia: a model for elucidating the dynamic regulation of ineffective erythropoiesis and iron metabolism - Ginzburg, Yelena (American Society of Hematology, 2011)
β-thalassemia is a disease characterized by anemia and is associated with ineffective erythropoiesis and iron dysregulation resulting in iron overload. The peptide hormone hepcidin regulates iron metabolism, and insufficient hepcidin synthesis is responsible for iron overload in minimally transfused patients with this disease. Understanding the crosstalk between erythropoiesis and iron metabolism is an area of active investigation in which patients with and models of β-thalassemia have provided significant insight. The dependence of erythropoiesis on iron presupposes that iron demand for hemoglobin synthesis is involved in the regulation of iron metabolism. Major advances have been made in understanding iron availability for erythropoiesis and its dysregulation in β-thalassemia. In this review, we describe the clinical characteristics and current therapeutic standard in β-thalassemia, explore the definition of ineffective erythropoiesis, and discuss its role in hepcidin regulation. In preclinical experiments using interventions such as transferrin, hepcidin agonists, and JAK2 inhibitors, we provide evidence of potential new treatment alternatives that elucidate mechanisms by which expanded or ineffective erythropoiesis may regulate iron supply, distribution, and utilization in diseases such as β-thalassemia.